Endosulfan induces autophagy and endothelial dysfunction via the AMPK/mTOR signaling pathway triggered by oxidative stress. (January 2017) - Zhang, Lianshuang; Wei, Jialiu; Ren, Lihua; Zhang, Jin; Wang, Ji; Jing, Li; Yang, Man; Yu, Yang; Sun, Zhiwei; Zhou, Xianqing
Abstract: Cardiovascular diseases is related to environmental pollution. Endosulfan is an organochlorine pesticide and its toxicity has been reported. However, the relationship between oxidative stress and autophagy induced by endosulfan and its underlying mechanism remain confusing. In this study, human umbilical vein endothelial cells (HUVECs) were chosen to explore the toxicity mechanism and were treated with 0, 1, 6, 12 μg/mL −1 endosulfan for 24 h, respectively. The present results showed that autophagy could be induced by endosulfan, which was verified by the monodansylcadaverine staining, autophagic ultrastructural observation, and LC3-I/LC3-II conversion. In addition, the levels of adenosine triphosphate (ATP), the mitochondria membrane potential (MMP) were significantly decreased in a dose-dependent way. The expression of proinflammatory cytokines (tumor necrosis factor α, interleukin-1β, and interleukin-6) were significantly elevated, and the index of endothelial function such as monocyte chemotactic protein 1 (MCP-1), intercellular cell adhesion molecule-1 (ICAM-1) increased. Moreover, endosulfan had an activation effect on the 5′AMP-activated protein kinase (AMPK)/rapamycin (mTOR) signaling pathway. Our findings demonstrated that endosulfan could induce oxidative stress and mitochondria injury, activate autophagy, induce inflammatory response, and eventually lead to endothelial dysfunction via the AMPK/mTOR pathway. This indicates that exposure to endosulfan is a potential risk factor for cardiovascular diseases. Graphical abstract: Highlights: Endosulfan induces autophagy of human umbilical vein endothelial cells. Endosulfan induces endothelial dysfunction of human umbilical vein endothelial cells. Endosulfan induces autophagy and dysfunction via the AMPK/mTOR signaling pathway of human umbilical vein endothelial cells.